2019
DOI: 10.1177/0269215518821718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quadriceps muscle neuromuscular electrical stimulation in living donor liver transplant recipients: phase-II single-blinded randomized controlled trial

Abstract: Objective: To evaluate the efficacy of neuromuscular electrical stimulation on quadriceps muscle strength and thickness in liver transplantation patients. Design: Phase-II, randomized, parallel-group, allocation-concealed, assessor-blinded, single-center controlled trial. Setting: Inpatient rehabilitation sector. Subjects: Patients following living donor liver transplantation. Interventions: The quadriceps muscle stimulation and the control groups received bilateral muscle electrical stimulation on the quadric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Further research into postoperative protein intake and physical activity will be essential for setting up a proper and feasible protocol to prevent patients suffering muscle loss [37,40]. Furthermore, a promising idea might be the application of neuromuscular electrical stimulation to muscles to maintain muscle thickness after surgery [46]. In conclusion, the current study demonstrated that surgery-related loss of muscle quantity or quality is present in more than half of the patients after liver resection for CRLM.…”
Section: Discussionmentioning
confidence: 81%
“…Further research into postoperative protein intake and physical activity will be essential for setting up a proper and feasible protocol to prevent patients suffering muscle loss [37,40]. Furthermore, a promising idea might be the application of neuromuscular electrical stimulation to muscles to maintain muscle thickness after surgery [46]. In conclusion, the current study demonstrated that surgery-related loss of muscle quantity or quality is present in more than half of the patients after liver resection for CRLM.…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that NMES improved muscle strength of the lower limb muscle group in seriously ill patients [26]. We have previously reported that NMES, combined with conventional physical therapy, significantly improved muscle mass in post-LDLT patients, as compared with physical therapy alone [15]. However, quadriceps muscle strength after LDLT was not sufficiently recovered, and ADL was not improved by this method.…”
Section: Discussionmentioning
confidence: 75%
“…NMES is a practical, passive therapy that can be safely applied to maintain quadriceps muscle mass in seriously ill patients [14]. We have previously reported that NMES, combined with conventional physical therapy, significantly improved muscle mass in post-LDLT patients, compared with physical therapy alone [15]. Furthermore, after LDLT, patients are frequently malnourished.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of malnutrition and sarcopenia among patients with BS may contribute to worse outcomes. 58 To mitigate the negative impacts of frailty, especially those due to sarcopenia, several studies demonstrated the effectiveness of physical training 59 or neuromuscular electrical stimulation 60 for recipients after LT. However, no reports yet demonstrate the impact of these pre-LT preparations as a part of the "prehabitation" program.…”
Section: Frailtymentioning
confidence: 99%